Study on Liver Neoplasia in Shih Tzu Dog: A Case Report - Ng, Audrey Jia Yie; Noviana, Deni; Latif, Hadri (Jurnal Veteriner; Vol 26 No 1 (2025), 2025)
Liver neoplasia is the excessive and uncontrolled replication of hepatocytes that forms nodules can visible in ultrasonography. The study was purposed to study and discuss the characteristic, diagnosis and treatment of liver neoplasm through the interpretation of ultrasonography and hematology in a Shih Tzu dog. Ultrasonography is conducted with a Chison Q8 ultrasound machine with a 5-7 MHz frequency convex probe on lateral recumbency. The blood cells, liver enzymes and nodules sizes were the main parameters in this study. The results in the period of three years from 2021-2023 were interpreted and supported with secondary data sources. The Shih Tzu dog is 14 years old in the year 2023 with a body weight of 5.21 kg. No obvious clinical signs were observed during previous examinations. However, lethargy, vomiting and anorexia were recorded in its latest examination. Thrombocytosis, granulocytosis, high liver enzymes and hypoglycemia, which are some of the neoplastic clinical manifestations, were also presented by this patient. Besides, liver neoplasm, spleen neoplasm and biliary sludge were seen in the sonogram findings of this patient. The liver and spleen neoplasm was observed stable, while the biliary sludge volume fluctuated. The treatment strategy recorded is Ondansetron, Samylin® (S-adenosil L-metionina (SAMe), silybin, vitamin E, and vitamin C), Ornipural and Ursodeoxycholic acid.